Developing the concept of maternal in teenage mothers: a hybrid model - Hoseini, Akram Sadat Sadat; Maleki, Maryam; Mardani, Abbas; Abbasi, Soheila (Frontiers in Psychology, 2024)
Objectives: Maternal transition is a challenging developmental process requiring physical, mental, social, and cognitive preparedness. Therefore, the transition to motherhood is even more challenging for teenagers who are exposed to both the maturation process and adaptation to the parenting role. Therefore, the present study was conducted to provide a deeper understanding of the maternal role in Iranian teenage mothers. Methods: A three-phase hybrid model was adopted for concept analysis. In the theoretical phase, 50 articles were analyzed. In the fieldwork phase, 10 participants were interviewed. In the final phase, the findings of the previous two stages were analyzed. This study was conducted between October 2021 and November 2022. After determining the attributes, antecedents, and consequences, a final definition was presented for parenting in teenage mothers. Results: The concept of motherhood for teenage mothers was described as “a process-oriented phenomenon in nature”, “complex, challenging and multidimensional”, “development with immature transition”, “a turning point in life”, “a stressful event”, “affected by several factors” and “bidirectional effects on life” according to antecedents, including “the level of received social support”, “reaction to teenage motherhood”, “teenage mother’s characteristics” and “family structure” leading to “positive psychological consequences”, “negative psychological consequences”, and “loss of educational and career opportunities”. Conclusions: This study provides a suitable ground for evaluating the concept of motherhood in teenage mothers and employing it in nursing care of teenage mothers and children by identifying this concept.